A “Young Farmer Problem”? Opportunities and Constraints for Generational Renewal in Farm Management: An Example from Southern Europe - Eistrup, Mathias (2019)
The existence of a “young farmer problem” in Europe has been recognized by scientists and policy-makers and is based on the widespread acknowledgement of the poor generational renewal rates in the farming sector and in particular in farmland management across the European Union. Despite existing support policy measures, young farmers (YF) face barriers which hamper the establishment and consolidation of their farming enterprises. Focusing on Alentejo (NUTS II), in Portugal, this paper identifies the difficulties YF face to accessing land, the high investment costs required to set up a farming unit, and the insufficient access to credit as the main reasons why young people are prevented from setting up their farming enterprises. Existing policy support measures targeting YF are widely perceived as inefficient with regard to triggering generational renewal. Hence, our findings suggest that not only is it necessary to pay greater attention to the complex question of land tenure, but that also the impact of policies implemented in the past should be examined in detail in order to develop and implement more effective measures that are sensitive to the different national and regional contexts